Regional Volume Tables for Duabanga grandiflora Walp. (Based on the Data of Manipur State) - Sharma, R. P.; Jain, R. C. (Indian Forester, 1977)
Volume tables of Duabanga grandiflora have been prepared by the method of linear regression. The model used is V=a+b D2H. Tables based on this model have been given.